2016
DOI: 10.3390/su8121280
|View full text |Cite
|
Sign up to set email alerts
|

Science, Technology and Innovation through Entrepreneurship Education in the United Arab Emirates (UAE)

Abstract: The purpose of this study is to investigate the ways of achieving Science, Technology and Innovation (STI) in UAE. Previously, sustainability within an entrepreneurship context has been related to economic viability as opposed to sustainability in its broadest sense. Through a survey research method, we have highlighted the effects of three independent variables and two intervening variables on three important outcomes, innovation, need for achievement and motivation, which ultimately contributes towards STI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 76 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…Universities being the hierarchal organizations have the access to the resources and have developed incubation centers for the support of its graduating students. These incubation centers provide students with the necessary resources to start and operate the business at the initial stages [ 46 ]. Further, universities help students to develop market-based competencies and resources to step into the market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Universities being the hierarchal organizations have the access to the resources and have developed incubation centers for the support of its graduating students. These incubation centers provide students with the necessary resources to start and operate the business at the initial stages [ 46 ]. Further, universities help students to develop market-based competencies and resources to step into the market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hayat and Amer (2013) found that student perception can be explained using the innovativeness, proactiveness, and risk-taking attributes of a teacher in Finland and Pakistan. Hameed et al (2016) found a strong need to revise the curriculum of higher education institutions in the UAE to develop self-confidence, locus of control, and risk-taking propensity among students. Winkler (2014) found that EE is a dynamic field of inquiry that considers the triadic reciprocal relationship of the personal, behavioral, and environmental factors of entrepreneurial learning.…”
Section: Literature Review Research On Competency Theorymentioning
confidence: 99%
“…Education and exposure to the actual entrepreneurship experience were seen to supersede indoctrination (Hameed et al 2016). Grassroots innovations are commercialized or scaled-up only rarely as innovators experience lack of tangible and intangible resources (Centre for Social Innovation (ZSI) 2016).…”
Section: Entrepreneurial Experience and Firm Innovativenessmentioning
confidence: 99%